EVALUASI PERESEPAN ANTIBIOTIK PASIEN INFEKSI SALURAN KEMIH DI INSTALASI RAWAT INAP RUMAH SAKIT ROEMANI SEMARANG - Hening Pratiwi; Septimawanto Dwi P (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2017)
ABSTRACTInappropriate antibiotics prescribing in Urinary Tract Infection (UTI) can lead antibiotic’s resistance. Hospitals should have a formulary as a reference for providing medical services to the patients. This study aimed to determine the types of antibiotics that prescribed for UTI treatment and determine the level of antibiotics prescribing conformity with the Roemani Semarang hospital’s formulary (2009) and WHO guidelines 2001. This study used a non-analytical descriptive design and retrospectively. The samples were 73 patients. This study includes the pattern of antibiotic prescribing in UTI patients and conformity with 2009 hospital formulary and 2001 WHO guidelines. The results showed that antibiotics are widely used cefotaxime (cephalosporins) 14 cases (19.18%), levofloxacin (quinolones) 11 cases (15.07%), and ceftriaxone (cephalosporins) 10 cases (13.70%). The combination that widely prescribed is a cephalosporins combination with quinolones three cases (4.11%), cephalosporin combination with other cephalosporins three cases (4.11%), and the combination of a cephalosporin with an aminoglycoside two cases (2.74%). There are 68 recipes (93%) suitable with hospital formulary, and five recipes (7%) not listed on the hospital formulary Roemani 2009. The UTI antibiotic monotherapy in women, men, and children do not exist in accordance with the WHO guidelines 2001. Key words: Urinary Tract Infections, antibiotics, hospital formulary, Roemani Hospital Semarang